Money justice - Daly, Kathleen (Journal of criminology, 2021)
Money justice?defined as money offered and paid to victims in the aftermath of wrongs?permeates society and everyday life. Current mechanisms of money justice are civil justice awards or out-of-court settlements for personal or cultural injury; redress programs or schemes for mass atrocities, political repression, historical injustice, and institutional abuse; and payments for war-related wrongs, terrorism, violent common crime, and contaminated blood products, among many others. In this article, we elucidate the concept of money justice, sketch the relationship of revenge and recompense in human history, distil relevant research, and put forward the money justice matrix, which provides a systematic way to analyse money payments (or lack of payments) in varied contexts of victimisation and with different justice mechanisms. Money justice is a new concept that analyses diverse wrongs studied in criminology, socio-legal studies, other social sciences, transitional justice, and historical injustice. Its contribution to new knowledge is two-fold. First, it will map and compare payments to survivors for diverse wrongs, investigate why payments differ, and assess inequalities in payments. Second, it will critically examine the money justice paradox. If, as victims say, money cannot recompense a wrong, why is money sought by victims and offered as justice? More generally, what does money achieve (or not achieve) as justice and for victims?